2018
DOI: 10.1103/physrevlett.120.207601
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Phase Precursors during a Photoexcited Insulator-to-Metal Transition in V2O3

Abstract: Here, we photoinduce and directly observe with x-ray scattering an ultrafast enhancement of the structural long-range order in the archetypal Mott system V_{2}O_{3}. Despite the ultrafast increase in crystal symmetry, the change of unit cell volume occurs an order of magnitude slower and coincides with the insulator-to-metal transition. The decoupling between the two structural responses in the time domain highlights the existence of a transient photoinduced precursor phase, which is distinct from the two stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 39 publications
(57 reference statements)
2
40
0
Order By: Relevance
“…In conclusion let us stress that recently discovered superconductivity in bilayer twisted graphene possibly also corresponds to the regime of BCS-BEC crossover between local and extended pairs in the d-wave channel (similarly to underdoped cuprates) but with anomalous chiral superconductivity of d+id type [177] which is in agreement with the phase diagram for idealized bilayer graphene in AB modification at low doping levels [20,22,23]. The discovery of superconductivity in graphene with many properties resembling the cuprates helps us to build the bridge between low temperature topological superconductors based on graphene [177] and bismuth [178][179][180] and vanadium oxides [181][182][183][184] which are very promising for superconducting nanoelectronics and quantum calculations (for creation of topologically protected qubits). The band structure calculations and recent experimental results show the evidence for multigap superconductivity in pressurized H3S hydrides as well as in the recently discovered high-temperature superconductor 10 LaH [84,85,86] where the superconducting dome occurs around the Lifshitz transition driven by pressure.…”
Section: Discussionsupporting
confidence: 71%
“…In conclusion let us stress that recently discovered superconductivity in bilayer twisted graphene possibly also corresponds to the regime of BCS-BEC crossover between local and extended pairs in the d-wave channel (similarly to underdoped cuprates) but with anomalous chiral superconductivity of d+id type [177] which is in agreement with the phase diagram for idealized bilayer graphene in AB modification at low doping levels [20,22,23]. The discovery of superconductivity in graphene with many properties resembling the cuprates helps us to build the bridge between low temperature topological superconductors based on graphene [177] and bismuth [178][179][180] and vanadium oxides [181][182][183][184] which are very promising for superconducting nanoelectronics and quantum calculations (for creation of topologically protected qubits). The band structure calculations and recent experimental results show the evidence for multigap superconductivity in pressurized H3S hydrides as well as in the recently discovered high-temperature superconductor 10 LaH [84,85,86] where the superconducting dome occurs around the Lifshitz transition driven by pressure.…”
Section: Discussionsupporting
confidence: 71%
“…This class of oxides bear the seed of a strong electronic correlation and have been widely studied since the early times of X-ray spectroscopy. The electronic transport and the spectroscopic properties of V2O3 [1], VO2 [2] as well as the complex local structure of V2O5 [3] have always attracted interest and still today their investigation is a hot topic in materials science, [4][5][6] with many potentials for technology applications [7]. Among the vanadium oxides, VO2 is one of the most stimulating system.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium dioxide (VO 2 ) and vanadium sesquioxide (V 2 O 3 ) are strongly electron-correlated materials that exhibit insulator-to-metal transitions (IMT) in equilibrium or non-equilibrium conditions [1,2]. In equilibrium, the IMT can be driven by temperature or pressure [3] and has been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the IMT in non-equilibrium conditions, as in the current driven transition, has attracted special attention due to extremely fast changes in electronic properties which generate strong electrical [4][5][6][7][8][9][10], optical [11][12][13], and magnetic responses [14][15][16][17]. Previous X-ray studies have demonstrated the existence of "hidden" non-equilibrium states in the photo-excited IMT of V 2 O 3 [2] as well as the separation of electric and structural transitions in VO 2 in the presence of electric fields [18]. The current driven IMT potentially offers a novel road to access these non-equilibrium states in future devices.…”
Section: Introductionmentioning
confidence: 99%